2018
DOI: 10.1101/337113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromomycin A2potently inhibits glucose-stimulated insulin secretion from pancreatic β cells

Abstract: words)Enhancers or inhibitors of insulin secretion could become therapeutics as well as lead to the identification of requisite -cell regulatory pathways and increase our understanding

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…We have recently observed that an important epigenetic reader protein TCF19, interacts with H3K4Me3 via its plant homeodomain (PHD) finger and recruits chromatin remodeling complex NuRD to repress gluconeogenic gene expression 4 . TCF19 is also found to be important in glucose‐stimulated insulin secretion (GSIS) 5 and causes repression of de novo glucose production in HepG2 cells 4 . TCF19 was initially discovered as a growth‐regulated cDNA 6 and was later shown to be involved in maintaining a fine balance between cell proliferation and apoptosis in mouse pancreatic β‐cells 7 .…”
Section: Introductionmentioning
confidence: 99%
“…We have recently observed that an important epigenetic reader protein TCF19, interacts with H3K4Me3 via its plant homeodomain (PHD) finger and recruits chromatin remodeling complex NuRD to repress gluconeogenic gene expression 4 . TCF19 is also found to be important in glucose‐stimulated insulin secretion (GSIS) 5 and causes repression of de novo glucose production in HepG2 cells 4 . TCF19 was initially discovered as a growth‐regulated cDNA 6 and was later shown to be involved in maintaining a fine balance between cell proliferation and apoptosis in mouse pancreatic β‐cells 7 .…”
Section: Introductionmentioning
confidence: 99%